Bioactive components in milk and dairy products - Park, Young W. (Wiley-Blackwell, 2009)
Although bioactive compounds in milk and dairy products have been extensively studied during the last few decades - especially in human and bovine milks and some dairy products - very few publications on this topic are available, especially in other dairy species' milk and their processed dairy products. Also, little is available in the areas of bioactive and nutraceutical compounds in bovine and human milks, while books on other mammalian species are non-existent. Bioactive Components in Milk and Dairy Products extensively covers the bioactive components in milk and dairy prod.
Keywords: Milk -- Composition.; Milk as food.; Dairy products in human nutrition.; Functional foods.; elektronické knihy; electronic books